Visualizing cellular secretion with single-protein sensitivity via interferometric scattering microscopy (iSCAT) - Gemeinhardt, André; König, Katharina; Nicoli, Francesca; Dahmardeh, Mahyar; Sandoghdar, Vahid (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Proteins are involved in a large number of biological processes. Apart from the field of proteomics, where ensemble studies of the entire set of proteins present in a system are carried out, detection and analysis of single proteins has become a vibrant field of research. Particularly, the study of proteins that are secreted from cells into the extracellular space is an important topic with wide implications for basic intercellular interactions and immunology. Secretory proteins are responsible for a vast amount of cellular functions involving migration, wound healing, immunological response, or intercellular communication. Challenges in the traditional methods such as immunoassays, Western blotting, mass spectrometry, or fluorescence microscopy are the need for labeling (with immunological complements, isotopes, or fluorescent markers) and the necessary processing and separation steps that hinder high temporal resolution in dynamic studies. Today, none of the existing techniques is able to detect single proteins secreted from living cells at subsecond temporal resolution without the need for labeling.
CRIS-Team Scopus Importer:2019-11-15